Diagnóstico hidráulico e hidrológico de las obras de drenaje vial en la ruta 29 nacional, tramo 29RSE Pereira- Santa Rosa de Cabal entre la abscisa K 10+145 a K10+687,7 en el departamento de Risaralda. (2021)
Diagnosing the design, capacity and operation of a section of road with its respective drainage works allows to know the conditions in which it is operating and thus determine if they are favorable for the road system to which it belongs; For this, the road section located in the El Rodeo sector was chosen, which has an extension of 542.6m and this serves as a return path for users of the coffee highway between the municipalities of Dosquebradas and Santa Rosa de Cabal.